Effect of Internal Controls on the Financial Performance of County Referral Hospitals in Kenya (Global Journal of Management and Business Research, 2021)
Internal Control Systems play an important role in every organization as it assists in realization of their financial performance goals. Most public institutions in Kenya have registered declining performance in recent years due to weakened internal control systems. Researches done relating to internal control systems and financial performance do not show directly the effect of corporate governance and regulatory systems on financial performance. The general objective of this study was to determine the effect of internal controls on the financial performance of county referral hospitals in Kenya. The specific objectives of the study were to determine the effect of physical controls on the financial performance of county referral hospitals in Kenya, to establish the effect of internal audit controls on the financial performance of county referral hospitals in Kenya, to assess the effect of corporate governance controls on the financial performance of county referral hospitals in Kenya and to determine the effect of regulatory controls on the financial performance of county referral hospitals in Kenya. The study used a descriptive correlational research design approach. The target population was 47 county referral hospitals in Kenya. Census was used to select all the 47 county referral hospitals in Kenya and purposive sampling was used to select the hospital accountant in each of the hospitals to make a sample size of 47 respondents.
Keywords: internal control systems; physical controls; internal audit controls; financial performance